Konsep Ruang Representasi Budaya pada Rancangan Pusat Kerajinan Kain Tenun Sasak, Sukarara, Lombok Tengah - Halim, Sultan Abbiyudani; Atika, Firdha Ayu; Azizah, Siti (Universitas Ciputra Surabaya, 2022)
Lombok Island is an island located in the Province of West Nusa Tenggara, the island of Lombok is one of the tourist destinations that attracts tourists who are famous for their natural beauty and culture. One of the cultural heritages on the island of Lombok is the woven cloth craft, which is one of the indigenous crafts on the island of Lombok, but the forum for promotion and marketing still does not represent the culture of the Sasak tribe and the surrounding environment, such as the lack of use of ornamentation, characteristics and others that related to the Sasan tribe and the surrounding environment, with the facts that have been discussed, research is carried out using qualitative descriptive methods, to increase production and marketing with the flow, namely, conducting studies from various sources related to the culture of the Sasak tribe, the surrounding environment, and tribal songket woven fabrics. sasak, studies related to space, such as space requirements to accommodate the production and marketing of woven fabrics, and what space will be needed to become a supporting forum for increasing the production and marketing of sasak woven fabrics, and conducting field studies in Sukarara Village, Central Lombok, and the village of sa de, Central Lombok, to study the space related to the production, promotion and marketing processes. The results of this design relate to three mutually sustainable spaces, namely, production space, gallery space, and retail space. The three spaces are able to become wheels to support the improvement of production and marketing processes, with a “representative” design theme. Each room certainly has a different function and spatial arrangement, but with the application of the concept of a representative space, the design object is able to indirectly give the impression of the same space in order to increase production and marketing, such as the use of songket woven fabric motifs as ornamentation in the space, the use of object images in the room. motifs of woven fabrics as furniture for the room, and the use of other things related to the culture of the Sasak tribe, such as musical instruments, space-forming materials, and carvings typical of the Sasak tribe.